Applying al-zughair transform on nuclear physics - A. Kuffi, Emad; Hassan Mohammed Mohammed, Ali; Qassim Majde, Ameer; Sabah Abbas, Elaf (International Journal of Engineering and Technology, 2020)
Al-Zughair transform is a novel transformation that is proposed in (2017), and due to its novelty it has not been applied to engineering fields, however Al-Zughair transform is capable to solve differential equations, for that reason it can be applied into engineering applications that include differential equations. In nuclear physics the radioactive decay of the atoms is well study subject, where there are many methods that are used to deal with it, however Al-Zughair transform has never been used before in that field, in this paper the differential equation of radioactive decay has been solved using Al-Zughair transform.Â Â